2016
DOI: 10.2217/fon-2016-0070
|View full text |Cite
|
Sign up to set email alerts
|

APF530 (Granisetron Injection Extended-Release) in a Three-Drug Regimen for Delayed CINV in Highly Emetogenic Chemotherapy

Abstract: APF530 versus the standard three-drug regimen provided superior control of delayed-phase CINV following HEC. ClinicalTrials.gov : NCT02106494.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 34 publications
8
35
0
Order By: Relevance
“…Ondansetron, the active comparator, has been used in large-scale CINV studies as the positive comparator for other 5-HT 3 RAs22,23 and is indicated for the prevention of nausea and vomiting associated with initial and repeat courses of emetogenic cancer chemotherapy, including high-dose cisplatin 24. In MAGIC, the APF530 arm demonstrated superior CR versus ondansetron in delayed CINV following HEC (64.7% vs 56.6%; P =0.014; 8% absolute improvement) 25. APF530 is the first and only 5-HT 3 RA to demonstrate superiority over another 5-HT 3 RA in a three-drug versus three-drug pivotal Phase III efficacy trial.…”
Section: Introductionmentioning
confidence: 88%
“…Ondansetron, the active comparator, has been used in large-scale CINV studies as the positive comparator for other 5-HT 3 RAs22,23 and is indicated for the prevention of nausea and vomiting associated with initial and repeat courses of emetogenic cancer chemotherapy, including high-dose cisplatin 24. In MAGIC, the APF530 arm demonstrated superior CR versus ondansetron in delayed CINV following HEC (64.7% vs 56.6%; P =0.014; 8% absolute improvement) 25. APF530 is the first and only 5-HT 3 RA to demonstrate superiority over another 5-HT 3 RA in a three-drug versus three-drug pivotal Phase III efficacy trial.…”
Section: Introductionmentioning
confidence: 88%
“…46 No 5-HT3 antagonists were administered on days 2 to 5. When administered subcutaneously, granisetron extended-release injection is effective for ≥5 days.…”
Section: Ae-a (2 Of 2)mentioning
confidence: 99%
“…Treatment-related injection site reactions (primarily bruising) occurred more frequently in patients who received GERSC than in those who received palonosetron, but these events were generally mild and resolved over time [17,18]. In the Phase III MAGIC trial comparing GERSC with ondansetron, each in a three-drug regimen with an NK-1 receptor antagonist and dexamethasone, GERSC was superior to ondansetron in complete response (no emesis or rescue medication) during the delayed phase of CINV in patients receiving HEC [19]. Both agents were well tolerated, and the incidence of injection site reactions was similar in both treatment groups [19].…”
mentioning
confidence: 99%
“…In the Phase III MAGIC trial comparing GERSC with ondansetron, each in a three-drug regimen with an NK-1 receptor antagonist and dexamethasone, GERSC was superior to ondansetron in complete response (no emesis or rescue medication) during the delayed phase of CINV in patients receiving HEC [19]. Both agents were well tolerated, and the incidence of injection site reactions was similar in both treatment groups [19]. GERSC is approved by the US FDA for use in combination with other antiemetics for the prevention of acute and delayed nausea and vomiting associated with initial and repeat courses of MEC or anthracycline and cyclophosphamidebased regimens [20].…”
mentioning
confidence: 99%
See 1 more Smart Citation